Preliminary Design of Wellhead Spacer Spool Based On the API Acceptance Criteria - Budi Baharudin; Rahman Hakim; Rahmat Hidayat; Mohammad Anas Fikri; Auliana Diah Wilujeng (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
In the case of assembly wellhead, a spacer spools was used to provide space and connect between parts of the wellhead. In order to design spacer spool with specified material should comply the standards and procedures of the oil and gas industry. The results of the material calculation were using the ASME BPVC guidelines. These three materials strengths were calculated if used as a body spacer spool. Based on acceptance criteria on API 6A 21st Edition, these three materials were categorized as acceptable to be used as a body spacer spool for this specification. These three materials strengths were also calculated the stress of the flange and flange rigidity criteria. Based on the acceptance criteria on ASME BPVC guidelines, the results showed that these materials can be used for flange because it had stress value under yield strength of material which was flange rigidity criteria for operating condition has 0.59 and 0.66 for testing condition because had value of rigidity that met with minimum acceptance criteria.